Feminist Collections, v.25, no.4 (summer 2004) - (:unkn) unknown (My University, 2004)
Subtitle: A Quarterly of Women's Studies Resources. 41p.
Contents: FROM THE EDITORS. STRONGER STUDENTS, BETTER RESEARCH: Information Literacy in the Women’s Studies Classroom, by Carroll Wetzel Wilkinson. GENDER STUDIES FOR A CIVIL SOCIETY: A RUSSIAN EXPERIENCE, by Elena Yakushkina. FEMINIST VISIONS: Videos Screened at “Women in the Middle: Borders, Barriers, Intersections” [2004 Conference, National Women's Studies Association]. E-SOURCES ON WOMEN & GENDER: By JoAnne Lehman. NEW REFERENCE WORKS IN WOMEN'S STUDIES: By Phyllis Holman Weisbard & Others. PERIODICAL NOTES: By JoAnne Lehman. ZINE AND TASTED: YUM, by M.L. Fraser. ITEMS OF NOTE: By Mary Pfotenhauer. BOOKS RECENTLY RECEIVED. INDEX TO VOLUME 25. Subscription Form.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews; Information Literacy; Civil Society--Russia; Videos; Zines; E-Sources